The Representation or the Heart. Philippe Lacoue-Labarthe, reader of Jean-Jacques Rousseau - Alarcón, Felipe (Re-presentaciones: Periodismo, comunicación y sociedad, 2023)
This article proposes a re-reading of Philippe-Lacoue Labarthe’s critique of Martin Heidegger in Poetics of History. To do so, we underline the role played by Jean-Jacques Rousseau in the emergence of a new thought of origin, and therefore of historicity, which Heidegger takes up despite the ignorance or contempt shown towards the author of The Social Contract. Heidegger, Lacoue-Labarthe writes, could not or would not read him with due seriousness. By following the operations of displacement and translation operated by Lacoue-Labarthe, this article seeks to explore the potentialities of the Rousseaunian corpus, as well as to provide elements for a new thinking of the relationship between tragedy and politics, or catharsis and Terror, allowing to give a new impulse to the question of representation, a question that has certainly crossed the entire history of philosophy.
Keywords: Representation; Catharsis; Origin; Jean-Jacques Rousseau; Martin Heidegger; Philippe Lacoue-Labarthe